Russia’s Defence Policy - Mr. Muhammad Sarmad Zia (CISS Insight Journal, 2017)
In the words of Emperor Aleksander III, “Russia has only two reliable allies — the army and navy.” The drafting of Russian Defence Policy is an intricate and heavily complex process that involves several factors and drivers. It has much to do with the country’s expansive territory, bordering North-Korea and China on its eastern flank and Europe on its western-side, its unique history of Soviet era and the subsequent disintegration, its nuclear power status and its ability to balance the global system. In the course of its shift from the Soviet Union to Russian Federation, it went through several changes vis-à-vis its political and economic systems. Under the new system, the president is the head of the state and exercises maximum control whereas the prime minister is essentially the head of government and appointed by the president.